NEW APPROACHES TO TEACHING “UZBEK LITERATURE” - Sayipova Dilobar Rakhimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
Literature teachers in higher education institutions should teach students to study independently, to work on and analyze information on their own. It is aimed at teaching students to actively participate in scientific discussions on current issues of "Uzbek literature", to participate in student scientific conferences, to prepare essays, competitions for literary anniversaries, electronic presentations, to write reviews of literary monographs, and to complete other tasks.